2012
DOI: 10.4038/sjdem.v2i2.4775
|View full text |Cite
|
Sign up to set email alerts
|

No link to cardiac valvulopathy was seen in cabergoline treated patients

Abstract: Objective: To evaluate the association between use of cabergoline in patients with prolactinoma and risk of developing clinically relevant cardiac valvular disease. Method: This was a descriptive cross sectional study conducted at Endocrinology and Pituitary clinics at National Hospital of Sri Lanka. Patients with macro and micro prolactinoma who were on medical therapy with cabergoline for more than 24 weeks duration were selected for the study. Patients with pre existing congenital valvular heart disease, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Approximately, 2000 prolactinoma patients on cabergoline (cumulative dose-mean: 152–465 mg, range: 15–3385 mg) have been studied for cardiac valvulopathy. [56789101112131415161718192021222324252627] None of the studies except one[10] have reported a higher prevalence of significant valvular regurgitation in cabergoline exposed prolactinoma patients compared to controls. In the study described by Colao et al .,[10] cabergoline exposed prolactinoma patients had significantly higher prevalence of moderate TR (54%) than healthy controls (0%).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 2000 prolactinoma patients on cabergoline (cumulative dose-mean: 152–465 mg, range: 15–3385 mg) have been studied for cardiac valvulopathy. [56789101112131415161718192021222324252627] None of the studies except one[10] have reported a higher prevalence of significant valvular regurgitation in cabergoline exposed prolactinoma patients compared to controls. In the study described by Colao et al .,[10] cabergoline exposed prolactinoma patients had significantly higher prevalence of moderate TR (54%) than healthy controls (0%).…”
Section: Discussionmentioning
confidence: 99%